Characteristics and Guardianship Status of Children Undergoing Forensic Medical and Psychological Evaluation for Asylum in Miami - Marina Plesons; Haley Hullfish; Priyashma Joshi; Stephen Symes; Anjali Saxena (Health and Human Rights)
To add to the limited evidence on forensic medical and psychological evaluations of children experiencing distress migration and seeking asylum in the United States, this paper describes the sociodemographic characteristics, nature of human rights violations, and guardianship status of the children served by the Human Rights Clinic of Miami from 2010 to 2021. Through a retrospective study of affidavits, we identified trends among sociodemographic characteristics and types of human rights violations and used bivariate analysis to determine factors associated with guardianship. Children constituted 17% of all evaluations conducted during this period. Approximately half were male, and two-thirds were aged 15–17 years. Honduras was the most common country of origin, and physical violence was the most reported human rights abuse, followed by gang violence. Most children reported being detained at the United States–Mexico border. Only a third had a guardian present during the evaluation, with guardianship significantly more likely for younger children. This study provides insight into the health needs of children affected by distress migration. It underscores how children’s experiences of forced migration and the barriers they face in accessing essential safeguards illustrate critical gaps in protecting their right to health.